The unrealised potential of Robert Browning's "Gold Hair: A Legend of Pornic". (2nd January 2022) - Hind, Heather
ABSTRACT: This article explores a hitherto neglected context of Robert Browning's "Gold Hair" (1864), analysing the poem in relation to the tradition of "hair harvests" in Brittany, France, as well as the broader contexts of the hair trade and hairwork in the nineteenth century. In doing so, it makes a case for reading the textual evocation of hair in the poem literally to trace a cultural shift towards hair framed in material rather than corporeal terms. The girl of the poem has abundant golden hair that corresponds with gold, hairwork, and the hair trade in ways that highlight its potential against the girl's apparent rejection of common hair practices. Diverging from previous analyses that have read poetic representations of hair in Browning primarily as symbolic (especially in relation to sexuality), the pairing of hair with gold is shown in this poem to signify unrealised sources of credit, unprocessed matter, holding the potential to be exchanged or refined. This article considers practices of keeping, working, and selling hair in conjunction with the Brownings' collection of hair and hairwork held by the Armstrong Browning Library, in this way elucidating the materiality of hair in both the poem and the Victorian imaginary.